Banking on Baghdad : - Black, Edwin (John Wiley & Sons, Inc., 2004)
In Banking on Baghdad, New York Times and international bestselling author Edwin Black chronicles the dramatic and tragic history of a land long the center of world commerce and conflict. Tracing the involvement of Western governments and militaries, as well as oil, banking, and other corporate interests, Black pinpoints why today, just as throughout modern history, the world nedds Iraq's resources - and remains determined to acquire and protect them. The book almost painfully documents the many ways Iraq's recent history mirrors its tumultuous past.